2005
DOI: 10.1021/jp0451142
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Modeling of the Reaction of C2H5 + O2

Abstract: Modeling of low-temperature ethane oxidation requires an accurate description of the reaction of C(2)H(5) + O(2), because its multiple reaction channels either accelerate the oxidation process via chain branching, or inhibit it by forming stable, less reactive products. We have used a steady-state chemical-activation analysis to generate pressure and temperature dependent rate coefficients for the various channels of this system. Input parameters for this analysis were obtained from ab initio calculations at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 59 publications
9
101
0
Order By: Relevance
“…These reaction pathways continue to be the focus of intense scrutiny and theoretical attention; for example, recent studies have shown [34][35][36] The MCH radical isomers are denoted by a number for a radical site on the ring or "X" for a radical site on the CH 3 group. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These reaction pathways continue to be the focus of intense scrutiny and theoretical attention; for example, recent studies have shown [34][35][36] The MCH radical isomers are denoted by a number for a radical site on the ring or "X" for a radical site on the CH 3 group. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, they have the structure of a methyl ester group attached to a long hydrocarbon chain of about [16][17][18][19] carbon atoms (C [16][17][18][19] H x -C(=O)O-CH 3 ). Due to their large size and their chemical/physical complexity (e.g., the introduction of the heterogeneous O atom compared to hydrocarbon fuels), detailed kinetic study on these biodiesel molecules is challenging both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, including that of Carstensen et al 41 on n-alkanes such as ethane and propane have highlighted the importance of the direct elimination of olefin and a hydroperoxyl from RO 2 .…”
mentioning
confidence: 99%